Aerosol-Synthesized Surfactant-Free Single-Walled Carbon Nanotube-Based NO2 Sensors: Unprecedentedly High Sensitivity and Fast Recovery - Kim, Sihyeok; Han, Jiye; Choi, Jin Myung; Nam, Jeong Seok; Lee, Il Hyun; Lee, Yeounggyu; Novikov, Ilya V.; Kauppinen, Esko I.; Lee, Keekeun; Jeon, Il (Advanced Materials, 2024)
This study pioneers a chemical sensor based on surfactant-free aerosol-synthesized single-walled carbon nanotube (SWCNT) films for detecting nitrogen dioxide (NO2). Unlike conventional CNTs, the SWCNTs used in this study exhibit one of the highest surface-to-volume ratios. They show minimal bundling without the need for surfactants and have the lowest number of defects among reported CNTs. Furthermore, the dry-transferrable and facile one-step lamination results in promising industrial viability. When applied to devices, the sensor shows excellent sensitivity (41.6% at 500 ppb), rapid response/recovery time (14.2/120.8 s), a remarkably low limit of detection (below ≈0.161 ppb), minimal noise, repeatability for more than 50 cycles without fluctuation, and long-term stability for longer than 6 months. This is the best performance reported for a pure CNT-based sensor. In addition, the aerosol SWCNTs demonstrate consistent gas-sensing performance even after 5000 bending cycles, indicating their suitability for wearable applications. Based on experimental and theoretical analyses, the proposed aerosol CNTs are expected to overcome the limitations associated with conventional CNT-based sensors, thereby offering a promising avenue for various sensor applications.
Keywords: Aerosol carbon; Aerosol carbon nanotube; FCCVD; Gas-sensors; NO2 gas detector; NO2 gas sensor; Single-walled carbon; Single-walled carbon nanotube; Surfactant-free; Synthesised; aerosol carbon nanotubes; FCCVD; NO2 gas detector; NO2 gas sensors; single-walled carbon nanotubes; wearable sensors